Temporary statutory staff in the health administration in Spain: the position of the Court of Justice of the European Union on successive recruitments without cause - Marín Alonso, Inmaculada (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The abuse in the temporary recruitment of health personnel in Spain has been uncovered by the European Court of Justice in several recent rulings. The last one goes beyond the debate on the application of the principle of equality and non-discrimination in working conditions in public employment between comparable permanent and temporary workers in the public administration and even goes as far as to question the objective causes that allow successive temporary contracts in the Spanish health recruitment of statutory staff to meet the permanent needs of the public health-care employer, it does not provide for measures to punish such abusive conduct, leaving it to the national courts to assess, in accordance with the rules of their applicable national law, the appropriate penalty to be imposed for such conduct. In such a case, the ECJ points out that both the conversion of temporary appointments into “non-permanent indefinite appointments” - even transforming the legal nature of the link to equate it in effect with the “non-fixed indefinite worker” in the public employment sector - and the award of compensation for dismissal are, inter alia, appropriate measures to prevent and punish abuses of temporary contracts. The final decision therefore rests with the internal judicial bodies, and the need for legislative reform in this area is clear
Keywords: statutory staff; temporary contracts; public health administration; contractual succession; sanctions for abusive behaviour